Feasibility of youth empowerment initiative for identifying never- and under-immunized children. (20th October 2021) - Bengali, R; Siddiqi, DA; Mehmood, M; Khan, AA; Baig, Q; Khan, AJ; Chandir, S
Abstract: Background: One-in-every 5 children globally remains deprived of life-saving vaccines. We developed and implemented the Adolescent Health and Leadership Program (AHLP) among school girls from grades 8-10 (Kiran Sitaras (KSs); Shining Stars) to provide them with soft skills and community mobilization skills and equipping them to become community advocates for immunization. We evaluated the feasibility of KS community mobilization through validating KSs' ability to accurately identify and link never- and under-immunized children with immunization services. Methods: We implemented a mixed-methods study in six public schools located in peri-urban areas of Karachi, Pakistan. After the development and roll-out of AHLP in schools, KSs conducted door-to-door visits in their neighborhoods to identify never-and under-immunized children. This was followed by verification visits by field staff to establish accuracy and immunization camps to vaccinate never- and under-immunized children identified by KSs. Results: From January 28 to February 22, 2020, 591 KSs visited 10, 330 households, screened 3, 295 under-2 children and identified 7.5% (247/3, 295) never- and 27.0% (889/3, 295) under-immunized children, with an accuracy of 90.4% and 49.6%, respectively. In January 2021, 291 never- and under-immunized children were invited to immunization camps, of which 28.9% (84/291) received vaccinations, while 57.0% (166/291) did not respond to the invite and 14.1% (41/291) were deemed ineligible (illness, overage, etc.). Conclusions: We demonstrated the feasibility of empowering adolescent girls to boost immunization uptake in LMIC settings. Engaging young women from within the community provides an organic and sustainable solution for promoting immunization coverage and equity today and ensuring they will continue to champion the cause in their capacity as tomorrow's mothers. We are actively scaling-up our solution across the country to create a force of 100, 000+ KSs to magnify our efforts. Key messages: The Kiran Sitara initiative, via its community-centered approach, leverages the force of adolescent school girls to boost demand and referrals for immunization in unreached geographical pockets. The Kiran Sitara initiative utilizes the power of youth engagement to identify never- and under-immunized children, and subsequently increase vaccine-uptake.